2005
DOI: 10.1021/ie049060u
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Trace Levels of Arsenic and Selenium from Aqueous Solutions by Calcined and Uncalcined Layered Double Hydroxides (LDH)

Abstract: The adsorption of As and Se from dilute aqueous solutions, representing model power-plant effluent streams, by calcined and uncalcined layered double hydroxide (LDH) adsorbents has been investigated. The results indicate that As(V) has a greater adsorption capacity than Se(IV) for both calcined and uncalcined LDHs. An mth-order kinetic rate equation describes the adsorption kinetics of As and Se on these adsorbents. The adsorption isotherms obey the Freundlich model. The adsorption capacities of As(V) and Se(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
208
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(233 citation statements)
references
References 34 publications
19
208
1
4
Order By: Relevance
“…Uncalcined carbonate-LDHs adsorbs more than 85% of As(III) and Cr(VI) [88,89]. The desorption of As(V) and Se(IV) was dependent on the anion species and their concentrations in the desorbing solutions [90].…”
Section: Heave Metal Capture In Liquid Wastementioning
confidence: 99%
“…Uncalcined carbonate-LDHs adsorbs more than 85% of As(III) and Cr(VI) [88,89]. The desorption of As(V) and Se(IV) was dependent on the anion species and their concentrations in the desorbing solutions [90].…”
Section: Heave Metal Capture In Liquid Wastementioning
confidence: 99%
“…Among the possible materials, transition metal oxides were studied extensively, such as MnO 2 , Co 3 O 4 , ZnO, and so on [9][10][11][12][13][14][15][16][17][18]. Layered double hydroxide (LDH) as a kind of heterostructure nanomaterials have shown superior properties in applications such as catalysis, sorption, medicine, and so on [19][20][21]. However, layered double hydroxide (LDH), as potential electrochemical active materials, its electrochemical properties is less studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported similar trends whereby the adsorption of As(III) on hydrotalcite was found to be consistent with the Langmuir model. 11,37) Moreover, the value of W s increased with increasing temperature. These results are in agreement with the present experimental data.…”
Section: )mentioning
confidence: 93%